Pengaruh Jumlah Anggota, Modal Sendiri dan Modal Pinjaman Terhadap Sisa Hasil Usah (SHU) Koperasi Unit Desa (KUD) Dikabupaten/Kota Provinsi Sumatera Barat - Arif Kurniawan; Yulhendri Yulhendri (Universitas Negeri Padang, 2020)
This study aims to find out 1) analyse the effect of the number of members on the remainder of the results of the business unit (SHU) village unit cooperatives (KUD), 2) To analyse the effect of their own capital on the residual results of the business unit (SHU) village unit cooperatives (KUD), 3) To analyse the effect of loan capital on the results of the remaining business units (SHU) of village unit cooperatives (KUD) of West Sumatra Province. The data used in this study are secondary data obtained directly from the statistical centre of West Sumatra Province. This study uses a time series method, namely from 2011-2017 and cross section totalling 19 districts / cities in West Sumatra Province. Data analysis method used in this study is panel data regression by testing the classical assumptions, including normality test, multicollinearity test, heteroscedasticity test, autocorrelation test with probability value (α) = 0.05. And statistical tests include t test, F test and testing the coefficient of determination (R2) with the value. The results of this study indicate that the number of members and their own capital have a significant influence on the residual income of village unit cooperatives (KUD), while loan capital does not significantly influence the residual income of village unit cooperatives (KUD) of West Sumatra Province.Keywords : SHU, number of members, own capital, loan capital.